Bioactive compounds and morphology in Opuntia spp. fruits from Portuguese ecotypes. - Reis, C.M.G. (2017)
The Opuntia spp. has minimal soil and water requirements, and the O. ficus-indica, in particular is sought to be an alternative for the Mediterranean region agricultural economy. The morphology, bioactive compounds and antioxidant properties of fruits were studied in twenty Portuguese ecotypes belonging to four Opuntia species (O. ficus-indica, O. robusta, O. dillenii and O. elata). The ecotypes were compared with the O. ficus-indica cultivars ‘Bianca’, ‘Gialla’ and ‘Rossa’. The fruits from Opuntia spp. ecotypes displayed variability in morphological and bioactive characteristics. Among O. ficus-indica ecotypes, the orange pulp fruits were larger, heavier and had a higher percentage of pulp as well as a lower percentage of seeds compared to the white pulp fruits. However, the weight of 100 seeds was lower in the white pulp ecotypes. The OFI-04 ecotype contrasted the other OFI ecotypes due to its pale yellow pulp, ovoid shape, and low seed weight per fruit as well as the amount of seeds as a percentage of pulp weight. The O. dillenii ecotypes had the highest betalain content, total phenolic compounds, and antioxidant activity, while O. elata had the highest ascorbic acid content. Both O. dillenii and O. elata had the highest acidity values. The red pulp cv. Rossa had the highest betalain content among the O. ficus-indica populations, followed by the orange and white pulp ecotypes. The highest amount of total phenolic compounds was found in the white pulp O. ficus-indica ecotypes. The hierarchical clustering analysis revealed that the ecotypes could be grouped into four major groups, and geographical origin was unrelated to the clustering pattern. This study provides original data on the morphology and bioactive compounds of Opuntia spp. fruits from Portuguese ecotypes.